2-Aminobenzoic acid–4-(pyridin-4-yldisulfanyl)pyridine (1/1) - Hadi D. Arman (Acta Crystallographica Section E, 2011)
The title 1:1 co-crystal, C7H7NO2·C10H8N2S2, features a highly twisted 4-(pyridin-4-yldisulfanyl)pyridine molecule [dihedral angle between the pyridine rings = 89.06 (10)°]. A small twist is evident in the 2-aminobenzoic acid molecule, with the C—C—C—O torsion angle being −7.7 (3)°. An N—H...O hydrogen bond occurs in the 2-aminobenzoic acid molecule. In the crystal, molecules are linked by O—H...N and N—H...N hydrogen bonds into a supramolecular chain along the b axis. These are connected into layers by π–π interactions occurring between pyridine rings [centroid–centroid distance = 3.8489 (15) Å]. The layers are connected along the a axis by C—H...O contacts. The crystal studied was a racemic twin.